(untitled) (Vietnam Journal of Community Medicine, 2023)
Objective: To analyze some factors associated with the knowledge and practices of food safety of street food handlers. Subjects and methods: A cross-sectional study was conducted on 290 street food handlers in Son Tay, Hanoi. Results: The proportion of subjects with good knowledge was 64.1%, and the proportion with good practices was 66.9%. The results of a multivariate analysis showed a significant association between knowledge and age (AOR: 1.75; 95% CI: 1.1-3.4), and participation in training (AOR: 2.31; 95% CI: 1.01-6.3). The factors of age (AOR: 1.75; 95% CI: 1.1-3.4), selling location (AOR: 1.75; 95% CI: 1.1-3.4), having a food safety commitment (AOR: 1.75; 95% CI: 1.1-3.4), and knowledge were all significantly associated with the practices of food handlers. Conclusion: The study showed that street food handlers’ food safety knowledge and practices are not high. The factors associated with street food handlers’ food safety knowledge and practices are age, training status, selling location, food safety commitment, and knowledge.